مهارات الحكمة الاختبارية وعلاقتها بالتحصيل الدراسي لدى طلبة كلية التربية/ ابن الهيثم للعلوم الصرفة (Journal Of Educational and Psychological Researches, 2013)
The aim of the stude is  to identify the skills wiseness test when the students of the College of Education / Ibn al-Haytham Science Pure, And to compare and identify   the differences in the skills of wiseness test according to sex when the students of the College of Education / Ibn al-Haytham Science Pure., As well as the comparison and identification of differences in the skills of wiseness test different scientific departments of the five among the students of the College of Education / Ibn al-Haytham / Science Pure. Finding correlation and the extent of the contribution of skills wiseness to test the collection of study. To investigate these goals has been building a measure of skills wiseness test be one of the seven components and (60) item test after checking characteristics psychometric scale (validity, reliability) measure applied to a sample of students from the College of Education Ibn al-Haytham Pure Sciences consisted of 400 male and female students and after obtaining the final grades to achieve the objectives of the research was reached the following conclusions                                                                         :1-There are no statistically significant differences between the average male and female in the use of the skills test wiseness.  2-Students of the college of Education Ibn al-Haytham possess the skills test and wisdom equal similar free resource.3-There are statistically significant differences between the students of the scientific departments in their use of the skills test wisdom. 4-A contribution to a positive and statistically significant at the level (0.05) to test skills of wisdom on academic achievement at the student sample.       Find reached some conclusions and recommendations and proposals.